Zachary Taylor papers - Taylor, Zachary, 1784-1850.
Correspondence, autobiographical account, military papers, estate papers, printed matter, map, and other papers. Subjects include Taylor's presidency, his service in the U.S. Army especially in the 2nd Seminole Indian War, and the management of Taylor's plantation, Fashion, Saint Charles Parish, Louisiana, by his son, Richard Taylor. Correspondents include John M. Clayton, George Washington Crawford, Jefferson Davis, Thomas Sidney Jesup, James K. Polk, Thomas W. Ringgold, and Winfield Scott.
Microfilm edition of Series 1-5 available
Microfilm produced from originals in Manuscript Division.
In part, photocopies.
U.S. president and army officer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Clayton, John M. -- 1796-1856 -- Correspondence; Crawford, George Washington, -- 1798-1872 -- Correspondence; Davis, Jefferson, -- 1808-1889 -- Correspondence; Jesup, Thomas Sidney, -- 1788-1860 -- Correspondence; Polk, James K. -- 1795-1849 -- Correspondence; Ringgold, Thomas W. -- Correspondence; Scott, Winfield, -- 1786-1866 -- Correspondence; Taylor, Richard, -- 1826-1879.; Taylor family; United States. -- Army; Indians of North America -- Wars -- 1815-1875.; Plantations -- Louisiana -- Saint Charles Parish; Seminole War, 2nd, 1835-1842.; United States -- Politics and government -- 1849-1853.; Army officers; Presidents -- United States